HUBUNGAN PENGETAHUAN DAN RIWAYAT PENYAKIT DENGAN KELAHIRAN PREMATUR DI RUMAH SAKIT UMUM DAERAH KOTA PADANGSIDIMPUAN - Wiwi Wardani Tanjung; Ayu Ulfah Nur Lubis (JIDAN (JURNAL ILMIAH KEBIDANAN), 2021)
The World Health Organization (WHO) reports that every year 13 million babies are born prematurely worldwide and one million babies die. The results of the 2013 Basic Health Research (Riskesdas) showed that 32.4% of infant deaths aged 0-6 days were caused by prematurity. Premature incidence in Padangsidimpuan City Hospital continues to increase from 2011-2014. The purpose of this study was to determine the relationship between knowledge and history of disease with premature birth at the Padangsidimpuan City General Hospital. This type of research is an analytic study with a cross sectional approach. The population was all mothers who gave birth prematurely and not prematurely at the Padangsidimpuan City Hospital. The sample in this study was the entire population of 92 people. The sample in this study amounted to 92 people. Data were collected through medical records and interviews using a questionnaire. Data were analyzed by univariate, bivariate using Chi-Square test at 95% confidence level (P < 0.05). The results showed that there was a relationship between medical history (p= 0.0001) and preterm birth, while the knowledge variable (p=0.061) was not related to preterm birth. It is recommended for health workers to further optimize health services by conducting antenatal care examinations according to standards to determine blood pressure, Hb levels, blood glucose in the prevention of preeclampsia, anemia, diabetes mellitus which can be at risk of prematurity. Padangsidimpuan City Hospital is expected to improve health counseling to mothers about a good age for pregnancy and childbirth, namely at the age of 20-34 years. The health office is expected to develop an atmosphere for community groups through perwiritan in socializing about prematurity